Analysis of soil physical factors on transient responses of overhead transmission lines subjected to lightning strikes - Tainá Fernanda Garbelim Pascoalato; Anderson Ricardo Justo de Araújo; Sérgio Kurokawa; José Pissolato Filho (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2023)
Several researchers have developed formulations to represent the soil electrical parameters (σg, εr) to compute ground-return parameters correctly and to obtain more accurate transient responses in power systems. This paper investigates the impact of the physical factors (frequency effect, water content, and porosity level) on σg, εr on transient responses in an overhead transmission line (TL) exposed to lightning strikes. For this purpose, four soil models are available in the literature to calculate σg, εr dependent on these physical factors. Transient voltages are calculated considering two approaches: Carson’s (C), which assumes a constant σg and disregards ground displacement currents, and Nakagawa’s (N), which includes the displacement currents with the σg, εr dependent on these physical factors. Results demonstrated that responses assessed with N differ significantly from those computed with C, being more pronounced for poorly-conducting soils. Further, including these physical factors is necessary as transient response waveforms are notably influenced when a realistic ground is assumed. These differences in the transient voltages may overestimate the insulation level of electrical components and equipment in electrical power systems.